Buckling of Elastomeric Beams Enables Actuation of Soft Machines. (21st September 2015) - Yang, Dian; Mosadegh, Bobak; Ainla, Alar; Lee, Benjamin; Khashai, Fatemeh; Suo, Zhigang; Bertoldi, Katia; Whitesides, George M.
Abstract : Soft, pneumatic actuators that buckle when interior pressure is less than exterior provide a new mechanism of actuation. Upon application of negative pneumatic pressure, elastic beam elements in these actuators undergo reversible, cooperative collapse, and generate a rotational motion. These actuators are inexpensive to fabricate, lightweight, easy to control, and safe to operate. They can be used in devices that manipulate objects, locomote, or interact cooperatively with humans.